Enteric Infections in Men Who Have Sex With Men. (13th April 2022) - McNeil, Candice J; Kirkcaldy, Robert D; Workowski, Kimberly
Abstract: Background: Enteric pathogens are often associated with exposure to food, water, animals, and feces from infected individuals. However, in sexual networks of men who have sex with men (MSM), transmission of enteric pathogens may occur during direct or indirect oral–anal contact. Methods: We performed a scoping review of the literature for studies prior to July 2019 with key terms for gastrointestinal syndromes ("proctitis, " "enteritis, " "proctocolitis"), enteric pathogens or sexually transmitted infections (STIs), and outbreaks using multiple electronic databases. Results: We identified 5861 records through database searches, bibliography reviews, and keyword searches, of which 117 references were included in the pathogen-specific reviews. Conclusions: The strength of observational data describing enteric pathogens in MSM and possible sexual transmission of enteric pathogens varies by pathogen; however, a robust body of literature describes the sexual transmission of Campylobacter, Giardia lamblia, and Shigella (particularly antimicrobial-resistant strains) in sexual networks of MSM. Providers are encouraged to consider enteritis or proctocolitis in MSM as possibly having been sexually transmitted and encourage targeted STI testing. Risk/harm reduction and prevention messages should also be incorporated, though there is an acknowledged paucity of evidence with regards to effective strategies. Further research is needed to understand the transmission and prevention of enteric pathogens in MSM.